Inequality and the Value of Public Natural Capital - Jasper N. Meya; Stefan Baumgärtner; Moritz A. Drupp; Martin F. Quaas (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study how income inequality affects the social value of a dynamic public good, such as natural capital. Our theory shows that both intra- and intertemporal inequality affect the social value of public natural capital. The direction and size of the effects are driven by the degree of substitutability between the public and private consumption goods. While the value of the public good increases (decreases) with intratemporal income inequality in the case of complements (substitutes), it increases (may decrease) with intertemporal income inequality for complements and Cobb-Douglas (substitutes). A problem of major relevance for the accounting of public natural capital as required by international treaties is to transfer values between study and policy contexts, or to up-scale values from study sites to the national scale. Our theory provides closed-form adjustment factors that allow controlling for differences in study and policy contexts.
Keywords: D63; H43; Q51; 330; dynamic public good; inequality; accounting; natural capital; environmental good; non-market valuation; WTP; benefit transfer; biodiversity